Teaching gene expression: an experience report with an investigative approach: Teaching gene expression: an experience report with an investigative approach (Health and Biosciences, 2025)
The teaching of subjects such as genetics and molecular biology faces significant challenges in the current educational context, especially when it comes to understanding complex topics such as gene expression. Educators need to update their teaching practices to promote more meaningful learning that goes beyond the mere transmission of information. The complexity of content such as gene expression, which involves fundamental concepts ranging from DNA structure to protein synthesis, is crucial to understanding biological processes and must be addressed in an accessible and contextualized manner. Authors highlight the need for more interactive and contextualized pedagogical approaches that stimulate students' curiosity and promote meaningful learning. Inquiry-based teaching, for example, allows students to formulate hypotheses and investigate, promoting more dynamic and meaningful learning. Thus, this report describes a teaching sequence applied in a 11th-grade class at a public state school, based on an investigative approach. The activity sought to stimulate hypothesis formulation using playful and accessible resources and guided discussions. The results indicated that, despite initial difficulties, students demonstrated conceptual advances and growing engagement, demonstrating the potential for effective inquiry-based teaching in the development of scientific and critical thinking.
Keywords: investigative activity; biology teaching; genetics; active methodologies; high school